KEPEMIMPINAN KURIKULUM - Halimatussa’diyah (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
School leaders also have the responsibility to carry out their leadership capacity in terms of curriculum leadership or curriculum leadership. Therefore, they must have basic knowledge of learning theory and curriculum, and even more importantly a clear understanding of school culture. The tasks in curriculum leadership are quite complex and challenging tasks. Curriculum developers and school leaders must have a certain amount of technical knowledge regarding curriculum concepts, processes and content. Curriculum developers and school leaders must be proactive in obtaining and securing all the necessary resources to support the curriculum development process. They must also ensure that teachers have adequate time, opportunity and staff to implement curriculum changes.